2021
DOI: 10.1162/neco_a_01426
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Fast and Slow Changes in Synaptic Weights from Simultaneously Observed Pre- and Postsynaptic Spiking

Abstract: Synapses change on multiple timescales, ranging from milliseconds to minutes, due to a combination of both short- and long-term plasticity. Here we develop an extension of the common generalized linear model to infer both short- and long-term changes in the coupling between a pre- and postsynaptic neuron based on observed spiking activity. We model short-term synaptic plasticity using additive effects that depend on the presynaptic spike timing, and we model long-term changes in both synaptic weight and baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Here we model the time-varying synaptic effect as a function of presynaptic ISI by fitting a generalized bilinear model (GBLM) to the postsynaptic spike trains. This model has been previously described (Ghanbari et al, 2017; Wei and Stevenson, 2021) and extends previous models of coupled GLMs (Harris et al, 2003; Truccolo et al, 2005; Pillow et al, 2008; Rebesco et al, 2010) to account for fluctuating excitability and plasticity. Briefly, for each connection, we model the postsynaptic firing rate γ at time t as y coup = n pre ∗ x coup where n pre and n post are the pre- and postsynaptic spike trains, respectively.…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…Here we model the time-varying synaptic effect as a function of presynaptic ISI by fitting a generalized bilinear model (GBLM) to the postsynaptic spike trains. This model has been previously described (Ghanbari et al, 2017; Wei and Stevenson, 2021) and extends previous models of coupled GLMs (Harris et al, 2003; Truccolo et al, 2005; Pillow et al, 2008; Rebesco et al, 2010) to account for fluctuating excitability and plasticity. Briefly, for each connection, we model the postsynaptic firing rate γ at time t as y coup = n pre ∗ x coup where n pre and n post are the pre- and postsynaptic spike trains, respectively.…”
Section: Methodsmentioning
confidence: 82%
“…Here β 0 ( t ) represents a time-varying baseline firing rate, which is estimated using an adaptive filtering algorithm (Wei and Stevenson, 2021). β s y slow ( t ) accounts for slow fluctuations that are shared by the presynaptic neuron and postsynaptic neuron, where y slow denotes a set of covariates generated by filtering the presynaptic spike train (cubic B spline functions with 4 equally spaced knots over 150 ms x slow ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lack of closed-form moments for the CMP distribution makes sampling computationally intensive. Here, to estimate Q robustly and quickly, we instead assume Q is diagonal and estimate it by maximizing the prediction likelihood in the filtering stage, as in [27].…”
Section: Estimating Process Noisementioning
confidence: 99%
“…By focusing on specific presynaptic spike patterns, such as pairs with specific inter-spike intervals (ISI), previous studies have shown how synaptic efficacy can vary depending on features of presynaptic spike timing (Usrey et al, 2000;Swadlow and Gusev, 2001;English et al, 2017). Modeling individual spike transmission probabilities for the entire spike train can also reveal how presynaptic spike features, as well as different types of plasticity, interact (Ghanbari et al, 2017(Ghanbari et al, , 2020Song et al, 2018;Wei and Stevenson, 2021).…”
Section: Introductionmentioning
confidence: 99%